Pengaruh Doktrin Konstruktivisme Budaya Bangsa Belanda Sebagai Negara Kolonialisme Terhadap Tipologi Bangsa Indonesia Sebagai Negara Post-Kolonialisme - Aftariansyah, Muhammad Diaz; Hanifa, Silma; Aepudin, Saepul (Gunung Djati Conference Series, 2025)
This research explores the significant impact and complex implications of Dutch colonial cultural constructivism on post-colonial Indonesia. Through a combined approach of historical analysis, literature review, and empirical case studies, the study unveils how the cultural constructivism of the colonial powers, such as the social classification of "native" and "non-native," education systems, and other cultural typologies, have doctrinally shaped the structures of social, political, and cultural identity that are still palpable and entrenched in the contemporary Indonesian societal constructs. These concrete findings underscore the crucial importance of a deeper understanding of colonial heritage in formulating effective policies and constructivism to address contemporary challenges, including social inequality, preservation of national identity, and the establishment of inclusive interethnic relationships. Utilizing qualitative methods, this research inherently acknowledges that reinforcing self-identity and solidifying identity is a necessity for any nation, while also providing valuable insights for policymakers, academics, and the general public on how colonial history continues to shape incidental social dynamics and determine political behavior patterns in Indonesia. This should ideally be done with the aim of paving the way for a more inclusive, flexible, and fair approach to national development in anticipation of Indonesia's golden future.